A transferência de risco de crédito em cadeias de suprimentos - Jorge, Ricardo Reolon (2010)
Made available in DSpace on 2010-04-20T20:08:02Z (GMT). No. of bitstreams: 1 71050100649.pdf: 1650593 bytes, checksum: 1aea540855dc6d99220fdb91c1e80900 (MD5) Previous issue date: 2009-07-16T00:00:00Z === This study aimed at verifying potential transfer of credit risks among companies in the context of supply chain, the time the maximum transfer happens, and its magnitude. A template formed by agile and lean supply chains were adopted in order to find significant differences among these two dimensions. The study was limited to two main links of the supply chains – manufacturers and retailers. The results showed that the credit risk transfer is observed in most of the cases, varying from upstream, downstream, and both directions. The time the maximum credit risk transfer also varied, showing great variability according to the type of the chain (agile or lean). The magnitude of the transfer shows the degree of influence of a link over the other in the analysis. === Este estudo teve com objetivo verificar a potencial transmissão de riscos de crédito entre empresas de uma mesma cadeia de suprimentos, o tempo em que ocorre a máxima transmissão e sua magnitude. As análises foram realizadas em cadeias de suprimentos conhecidas pela academia como cadeias enxutas e cadeias ágeis, limitando-se aos dois elos principais das cadeias selecionadas – comércio e indústria. Os resultados mostraram que a transmissão de risco de crédito é observável na maioria dos casos, ora a jusante, ora a montante, ora bilateralmente. Os prazos em que ocorre a máxima transferência também foram identificados e apresentaram grande variabilidade segundo o tipo de cadeia estudada (enxuta ou ágil). A magnitude da transmissão mostra o grau de influência de um nó da cadeia sobre o outro constante na análise.